What fo you do with a kangaroo? - Mayer, Mercer (New York : Scholastic Inc, 1979)
If the bossy kangaroo jumped through your window and started telling you what to do AND refused to go away AND had all kinds of other animals joining him . . . what would you do?
Keywords: Kangaroos-Fiction